Існування та стійкість періодичних розв'язків ланцюгів зв'язаних осциляторів - Майстренко, Ю.Л.; Попович, О.В. (Український математичний журнал, 1997)
We consider a nonlinear system of difference equations. This system corresponds to chains of N symmetrically connected oscillators with sufficiently general type of connection, which includes, among others, local and global connection. We prove a theorem on the existence and stability of space-time periodic solutions of such systems for sufficiently small values of the parameter of connection ɛ.